2021
DOI: 10.3389/fmicb.2021.760255
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Treatment, Mechanisms for Failure, and Adjunctive Therapies for Infections by Group A Streptococcus

Abstract: Group A Streptococcus (GAS; Streptococcus pyogenes) is a nearly ubiquitous human pathogen responsible for a significant global disease burden. No vaccine exists, so antibiotics are essential for effective treatment. Despite a lower incidence of antimicrobial resistance than many pathogens, GAS is still a top 10 cause of death due to infections worldwide. The morbidity and mortality are primarily a consequence of the immune sequelae and invasive infections that are difficult to treat with antibiotics. GAS has r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 125 publications
0
23
0
6
Order By: Relevance
“…Other potential advantages of clindamycin for the treatment of iGAS include: (a) clindamycin is associated with a longer postantibiotic effect than beta-lactam agents, and (b) clindamycin suppresses the synthesis of penicillin binding proteins, which are involved in cell wall synthesis and degradation ( 34 ). Clindamycin also has non-antimicrobial antibiotic effects such as the inhibition of M-protein synthesis, superantigens and other toxins ( 35 ). Clindamycin, together with β-lactams, is considered to be effective in the treatment of necrotizing fasciitis or STSS ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other potential advantages of clindamycin for the treatment of iGAS include: (a) clindamycin is associated with a longer postantibiotic effect than beta-lactam agents, and (b) clindamycin suppresses the synthesis of penicillin binding proteins, which are involved in cell wall synthesis and degradation ( 34 ). Clindamycin also has non-antimicrobial antibiotic effects such as the inhibition of M-protein synthesis, superantigens and other toxins ( 35 ). Clindamycin, together with β-lactams, is considered to be effective in the treatment of necrotizing fasciitis or STSS ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clindamycin also has non-antimicrobial antibiotic effects such as the inhibition of M-protein synthesis, superantigens and other toxins ( 35 ). Clindamycin, together with β-lactams, is considered to be effective in the treatment of necrotizing fasciitis or STSS ( 35 , 36 ). An Australian prospective study suggested that adding clindamycin could reduce mortality ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…GAS expresses various virulence factors to subvert the host innate immune system, which is central to controlling GAS infection ( 3 ). Since current treatment strategies are failing ( 4 ), there is a need to further examine the (dys)regulation of host immune networks underlying GAS pathophysiology and identify novel therapeutic targets to arrest disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…However, GAS has been shown to survive intracellularly in macrophages during both acute invasive soft tissue infection and asymptomatic carriage (3)(4)(5). Although GAS remains highly sensitive to beta-lactam antibiotics, the gold standard of treatment (6), the ability of bacteria to persist in macrophages and re-emerge after antibiotic treatment poses a therapeutic challenge (4).…”
Section: Introductionmentioning
confidence: 99%